“A place where no woman has ever entered…” The unique spiritual heritage of the Athos peninsula in the context of history and present time - Peter Caban (Polonia Sacra)
Christian spirituality was perceived differently in the whole history of Church. When we look at the spiritual heritage of Christianity, a special position is given to a unique spiritual and geographic locality – the state of monks – Athos peninsula. It is a beautiful place where no woman has ever entered. This contribution aims to describe and interpret the religious heritage of this spiritually unique place. It is perceived as a protected area and the centre of eastern spirituality. It will be described on the basis of Church history as well as on the basis of personal experience of the author who visited Mount Athos and scientifically explored the sources.